The strength of weak embodiment (2018)
in light of evidence arguing against strong forms of embodiment. Among other things, the embodiment approach breaks away from the Cartesian ontology of the modulatory system. We claim that the advantages of the embodiment approach are: a) it grounds cognition into modal experience, b) it is harmonious with a materialist philosophy of mind (emergent materialism), and c) it is supported by experimental research in various fields. However, embodiment must still address abstractions, theoretical misunderstandings (representations vs non-representations) and neuroscientific findings that challenge the extension and relevance of sensorimotor properties into cognitive processes. While the strong version of embodiment is seriously challenged by conceptual and physiological setbacks, its weak version is supported by compelling evidence. We suggest future research focus on the psychophysiological bases of grounded cognition and redirect efforts towards the field of cross-modal correspondence.